2022
DOI: 10.3389/fpubh.2022.974281
|View full text |Cite
|
Sign up to set email alerts
|

Applying formative evaluation in the mentoring of student intern nurses in an emergency department

Abstract: ObjectiveTo explore the effectiveness of formative evaluation in the mentoring of student nursing interns in an emergency department.MethodsA total of 144 intern nursing students in the emergency department of a tertiary care hospital in Fuzhou were selected as the study subjects from July 2020 to February 2021. Adopting quasi-experimental studies methods, the students were divided into the experiment group (n = 74) and the control group (n = 70), based on their practicing rotation times. Formative evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nurses developed their clinical competence through in-house education and learning sessions within the area of Practice (Suprapto, 2022). It is also suggested that nurses develop their skills and learning abilities during the formative stages of their Practice (Zhang et al, 2022). In-house education and the formative stages of nursing practice focus on the early stages of the nurse's professional career, usually the first three years; this suggests that nurses' full potential is only being developed when they are already in their practice.…”
Section: A Related Literature the Filipino Nursing Education And Trai...mentioning
confidence: 99%
“…Nurses developed their clinical competence through in-house education and learning sessions within the area of Practice (Suprapto, 2022). It is also suggested that nurses develop their skills and learning abilities during the formative stages of their Practice (Zhang et al, 2022). In-house education and the formative stages of nursing practice focus on the early stages of the nurse's professional career, usually the first three years; this suggests that nurses' full potential is only being developed when they are already in their practice.…”
Section: A Related Literature the Filipino Nursing Education And Trai...mentioning
confidence: 99%